Correlation complexation constants of Ce4+ and F−. Issue 1 (November 2020) - Jiang, Ying; Wang, Xuemei; Chen, Yunzhu; Nengzi, Lichao
Abstract: Measured CeFn (n=1, 2, 3) complexation constant and solubility product constant of CeF4 and Na2 CeF6 by ICP-AES and UV spectrophotometer, when Ce 4+ and F − complexation reaction in water medium and nitric acid medium respectively, and the effects of Re 3+ and nitric acid concentration on Ce 4+ and F − complexation reaction were studied. The experimental results show that the first-order complexation constant of Ce 4+ and F − is CeF3 + =6.94*10 6, the second-order complexation constant is CeF2 2+ =4.541*10 11, and the third-order complexation constant is CeF3 + =6.232*10 14 . Compared with the complexation reaction of Ce 4+ and F − in water medium and nitric acid medium, the complexation reaction of Ce 4+ and F − in nitric acid medium is better. Re 3+ appears, which affects the complexation reaction between Ce 4+ and F − . When in nitric acid medium, the higher the concentration of nitric acid, the more unfavorable the complexation of Ce 4+ and F − . The study of the relevant physical constants of Ce 4+ and F − in this paper can be helpful for the separation of Ce 4+ and F −, enrich the physical and chemical information of rare earth elements, and provide the basic theoretical basis for the rare earth fluoride that is difficult to be separated and recovered from the tailings, so as to reduce the harm to the soil environment.